Tinjauan Yuridis Peranan Pemerintah Daerah Dalam Mewujudkan Pemerintahan Yang Baik Dalam Bidang Perizinan Pariwisata - Pratama, Amri; Minin, Darwinsyah; Isnaini, Isnaini (ARBITER: Jurnal Ilmiah Magister Hukum, 2019)
The purpose of this study is to examine the tourism sector that is continuously being developed by the government as a pillar of national development because it is able to sustain the national economy when the world is experiencing a crisis. In Law Number 10 Year 2009 it is stated that tourism development is needed to encourage equal opportunity to try and benefit and be able to face the challenges of changing local, national and global life. Medan City as one of the autonomous regions in Indonesia which when viewed in terms of spatial planning, then almost 70% is a densely populated residential area. The growth of the tourism sector in the city of Medan, does not originate from natural tourist attractions like other areas in general, but rather to city tourism, such as nightclubs, hotels, hangout places, cafes, restaurants and salon and spa places. The industry has become one of the reliable projects of the City of Medan to increase regional revenues of the City of Medan. The tourism license of the City of Medan has been regulated in law No. 19 of 2009 concerning Tourism, Law No. 23 of 2014 concerning Regional Government. And Regional Regulation of Medan City No. 4 of 2014 concerning Tourism. The role of the local government in realizing good governance in the field of tourism is to provide infrastructure, expand various forms of facilities and regulate and promote the public both at home and abroad in matters relating to the tourism industry in the city of Medan